Fences on the Epistemological Prairie: A Settler Colonial Approach to “Religion and Science” - Stenmark, Lisa L. (Religions, 2025)
Building on the idea of religion and science as conceptual maps of intellectual territory, I use a settler colonial analysis as a framework for thinking about decolonizing religion and science in a way that moves away from abstraction and towards action; addressing not just the ideas, but the tools of control—the fences—that impose ideas on the territory itself. Comparing the Wyoming prairie with the epistemological prairie, I describe the maps, fences and other tools and technologies of settler colonialism used to appropriate Indigenous Land and knowledge, eventually turning it into private property. It is in this last step—the creation of private property—that fences are most important, because they are tools of ownership that do not merely restrict access to parts of the prairie (land and knowledge), but restrict movement on the prairie itself. I describe patents and intellectual property as examples of fences on the epistemological prairie. Because they are legally and historically connected to technologies of settler colonial appropriation of land—including terra nullius and land patents—they are an excellent example of the connection between land and epistemological territory, and show what epistemological decolonization can look like in practice.